Enabling innovative environmental community-based research: A vision for the next International Polar Year 2032–2033 - Louise Mercer; Michael Lim; Dustin Whalen; Deva-Lynn Pokiak; Paul J. Mann (Environmental Science & Policy, 2026)

Microvertebrates from the Rhaetian bone beds at the Carrefour site, Patchway, near Bristol - Lavanya Ralhan; Joseph L. Mercer; Christopher J. Duffin; Claudia Hildebrandt; Tim Tomkinson; Deborah Hutchinson; Sue Swansborough; Michael J. Benton (Proceedings of the Geologists' Association, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Molecular epidemiology and evolution of norovirus in Australia and New Zealand, 2018 to 2020 - Grace J. H. Yan; Joanne Hewitt; Lewis K. Mercer; Emma F. Harding; Dawn Croucher; Alice G. Russo; Peter G. Huntington; Jason M. Mackenzie; William D. Rawlinson; Peter A. White (Infectious Diseases, 2025)

Distribution and disturbances of ditches across salt marshes of the Northeast U.S. with implications for management and restoration - Erin K. Peck; Julie E. Walker; Katherine V. Ackerman; Joel Carr; Maureen D. Correll; Zafer Defne; Linda A. Deegan; Mitchell J. Eaton; Neil K. Ganju; Mitch Hartley; Catherine Johnson; Jason Mercer; et al. (Journal of Environmental Management, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Differential impact of perfluorooctanoic acid and fluorotelomer ethoxylates on placental metabolism in mice - Haley Adams; Jenna Hanrahan; Sophie Kiefte; Thomas O'Brien; Grace V. Mercer; Katherine L. Steeves; Céline M. Schneider; Karl J. Jobst; Lindsay S. Cahill (Chemosphere, 2024)

Spatial patterns of sediment contamination and their influence on benthic infaunal communities in a highly tidal and industrial estuary in Atlantic Canada - Andrew J. Guerin; Karen A. Kidd; Marie-Josée Maltais; Angella Mercer; Heather L. Hunt (Marine Pollution Bulletin, 2024)

Perceptions of weather-based pain forecasts and their effect on daily activities - Christopher J. Elcik; Christopher M. Fuhrmann; Scott C. Sheridan; Kathleen Sherman-Morris; Andrew E. Mercer (International Journal of Biometeorology, 2024)

Temporal and Spatial Trends in Benthic Infauna and Potential Drivers, in a Highly Tidal Estuary in Atlantic Canada - Andrew J. Guerin; Karen A. Kidd; Marie-Josée Maltais; Angella Mercer; Heather L. Hunt (Estuaries and Coasts, 2023)
Infaunal invertebrate communities of coastal marine sediments are often impacted by human activities, particularly in harbours and estuaries. However, while many studies have attempted to identify the key factors affecting benthic infauna, few have done so for highly energetic tidal estuaries. Samples were collected over a decade (2011–2020) from a series of reference sites in Saint John Harbour (45.25° N, 66.05° W), a highly tidal estuary in the Bay of Fundy, Canada. These data were used to examine spatial and temporal trends in infaunal invertebrate communities and sediment properties and to determine the extent to which the biological patterns were driven by measured physical and chemical variables. There were substantial differences among sites in infaunal invertebrate abundance (median ranging from 688 to 13,700 individuals per square meter), infaunal species richness (median ranging from 8 to 22), and Shannon diversity (median ranging from 1.26 to 2.34); multivariate analysis also revealed variation in species composition among sites. Sediment contaminant concentrations also varied among sites, but differences tended to be smaller (e.g. median chromium concentrations ranging from 21.6 to 27.6 mg/kg). Sample contaminant concentrations were all below probable effect levels, and almost all below threshold effect levels (Canadian interim sediment quality guidelines), but relationships with biological data were still detectable. However, physical variables (depth, sediment characteristics) were better predictors of biological variables and community composition. These results confirm the importance of physical factors in shaping infaunal communities in soft-sediment habitats in tidally influenced coastal waters.

Shelf break exchange processes influence the availability of the northern shortfin squid, Illex illecebrosus , in the Northwest Atlantic - Sarah L. Salois; Kimberly J. W. Hyde; Adrienne Silver; Brooke A. Lowman; Avijit Gangopadhyay; Glen Gawarkiewicz; Anna J. M. Mercer; John P. Manderson; Sarah K. Gaichas; Daniel J. Hocking; Benjamin Galuardi; Andrew W. Jones; et al. (Fisheries Oceanography, 2023)
The United States Northern Shortfin squid fishery is known for its large fluctuations in catch at annual scales. In the last 5 years, this fishery has experienced increased availability of Illex illecebrosus along the Northeast US continental shelf (NES), resulting in high catch per unit effort (CPUE) and early fishery closures due to quota exceedance. The fishery occurs within the Northwest Atlantic, whose complex dynamics are set up by the interplay between the large‐scale Gulf Stream, mesoscale eddies, Shelfbreak Jet, and shelf‐slope exchange processes. Our ability to understand and quantify this regional variability is requisite for understanding the availability patterns of Illex , which are largely influenced by oceanographic conditions. In an effort to advance our current understanding of the seasonal and interannual variability in this species' relative abundance on the NES, we used generalized additive models to examine the relationships between the physical environment and hotspots of productivity to changes in CPUE of I. illecebrosus in the Southern stock component, which comprises the US fishery. Specifically, we derived oceanographic indicators by pairing high‐resolution remote sensing data and global ocean reanalysis physical data to high‐resolution fishery catch data. We identified a suite of environmental covariates that were strongly related to instances of higher catch rates. In particular, bottom temperature, warm core rings, subsurface features, and frontal dynamics together serve as indicators of habitat condition and primary productivity hotspots, providing great utility for understanding the distribution of Illex with the potential for forecasting seasonal and interannual availability.

Mechanisms and models for industry engagement in collaborative research in commercial fisheries - Matthew R. Baker; Robert Alverson; Ruth Christiansen; Keith Criddle; Danny Eilertsen; Robert J. Foy; John Gauvin; Scott E. Goodman; Leigh Habegger; Bradley P. Harris; Nicole Kimball; Anna Malek Mercer; et al. (Frontiers in Marine Science, 2023)
Data and insights from fishers are essential sources of information to advance understanding of fishery and ecosystem dynamics. Incorporating fisher and industry knowledge holds prospects for improving marine science and fisheries management. We address cooperative research in the context of collaboration between fishers, scientists, industries, universities, and agencies to develop applied research to understand marine ecosystems, inform fishery management, enhance sustainability, govern resource use, and investigate social-economic dynamics. We leverage the insights of more than 100 research scientists, fisheries managers, industry representatives, and fishers to outline actionable recommendations for effective approaches and mechanisms to integrate industry data, perspectives, and insights in fisheries science. We also highlight opportunities and address challenges and limitations to such collaboration.

Titanium and chromium isotopic compositions of calcium-aluminum-rich inclusions: Implications for the sources of isotopic anomalies and the formation of distinct isotopic reservoirs in the early Solar System - Zachary A. Torrano; Gregory A. Brennecka; Cameron M. Mercer; Stephen J. Romaniello; Vinai K. Rai; Rebekah R. Hines; Meenakshi Wadhwa (Geochimica et Cosmochimica Acta, 2023)

Bringing in the experts: application of industry knowledge to advance catch rate standardization for northern shortfin squid (Illex illecebrosus) - Anna J. M. Mercer; John P. Manderson; Brooke A. Lowman; Sarah L. Salois; Kimberly J. W. Hyde; Jeffrey Pessutti; Andrew W. Jones; Robert Ruhle; Bill Bright; Troy Sawyer; Meghan Lapp; Jeff Kaelin; et al. (Frontiers in Marine Science, 2023)
Sources of fisheries information outside of fishery-independent surveys (e.g. fishery-dependent data) are especially valuable for species that support productive fisheries and lack reliable biological information, such as the northern shortfin squid ( Illex illecebrosus ). Fishery-dependent data streams are available for most species, however collaboration with industry members is critical to ensure that these fishery-dependent data are collected, applied, and interpreted correctly. Despite the need for collaboration and the frequency that fishery data are used in scientific research, there is limited literature on the structure of interactions and knowledge sharing that inform the analysis and application of fishery data. Between 2019 and 2022, a group of researchers collaborated with members of the northern shortfin squid fishing industry to bring together research data sets and knowledge from harvesters and processors to better describe the fishery dynamics, distribution, life history, and oceanographic drivers of the species. The collaboration focused on developing custom standardized fishery catch per unit effort (CPUE) indices to provide indicators of population trends that accounted for the impacts of technical and economic aspects of harvesting, processing and marketing on fishing effort, selectivity and landings of northern shortfin squid. We describe the methods used to inform and interpret the CPUE analyses, focusing on novel structure of interactions we had with industry members, and suggest best practices for integrating industry knowledge into CPUE standardization. The information shared and research products produced through this science-industry research collaboration advanced understanding of northern shortfin squid population and fishery dynamics, and contributed directly to the 2022 stock assessment and management process. Given the complex and stochastic nature of the northern shortfin squid population and fishery, we found it critical to maintain open communication and trust with processors and harvesters, who have unique insight into the factors that may be driving changes in catch, landings, and productivity of the valuable resource species.

Seasonal changes of trace elements, nutrients, dissolved organic matter, and coastal acidification over the largest oyster reef in the Western Mississippi Sound, USA - M. S. Sankar; Padmanava Dash; YueHan Lu; Xinping Hu; Andrew E. Mercer; Sudeera Wickramarathna; Wondimagegn T. Beshah; Scott L. Sanders; Zikri Arslan; Jamie Dyer; Robert J. Moorhead (Environmental Monitoring and Assessment, 2023)

Next-generation Tumor-homing Induced Neural Stem Cells as an Adjuvant to Radiation for the Treatment of Metastatic Lung Cancer - Alison R. Mercer-Smith; Andrew Buckley; Alain Valdivia; Wulin Jiang; Morrent Thang; Noah Bell; Rashmi J. Kumar; Hunter N. Bomba; Alex S. Woodell; Jie Luo; Scott R. Floyd; Shawn D. Hingtgen (Stem Cell Reviews and Reports, 2022)

Mitogenomics reveals low variation within a trigeneric complex of black corals from the North Pacific Ocean - Yessenia M. Bledsoe-Becerra; Iesha S. Whittaker; Jeremy Horowitz; Katherine Medina Naranjo; Jicayla Johnson-Rosemond; Kristen H. Mullins; Karena M. Cunningham; Suchir Shetty; Samuel N. Messinides; Melinda S. Behney; Jessica A. Fehsal; Ashley N. Watson; et al. (Organisms Diversity & Evolution, 2022)

Cover Image - Lewis K. Mercer; Emma F. Harding; Grace J. H. Yan; Peter A. White (Journal of Fish Diseases, 2022)

Novel viruses discovered in the transcriptomes of agnathan fish - Lewis K. Mercer; Emma F. Harding; Grace J. H. Yan; Peter A. White (Journal of Fish Diseases, 2022)

Learning From the Study Fleet: Maintenance of a Large-Scale Reference Fleet for Northeast U.S. Fisheries - Andrew W. Jones; Katie A. Burchard; Anna M. Mercer; John J. Hoey; Michael D. Morin; Giovanni L. Gianesin; Jacob A. Wilson; Calvin R. Alexander; Brooke A. Lowman; Debra G. Duarte; David Goethel; James Ford; et al. (Frontiers in Marine Science, 2022)
Logbook data from commercial fisheries are a vital component in the machinery of management, including tracking the volume of catches and allocating catch spatially. At the same time, logbooks can provide a unique window into the ecological and sociological conditions in marine fisheries, where fishermen interact with marine species and environments frequently and broadly. Traditional logbooks, however, often are not sufficiently standardized (when personal logs), or lack the detail (when regulatory documents) required to adequately understand fisheries ecosystems. The Study Fleet program, operated by the Northeast Fisheries Science Center’s Cooperative Research Branch, was developed to address these shortfalls by engaging members of the fishing industry in collecting high-resolution catch, effort, and environmental data using electronic logbooks. Since its inception, the Study Fleet has expanded from a small project focused on collecting detailed catch information from the New England multispecies groundfish fishery to a program with a wider scope encompassing a variety of fisheries, gears, and environmental parameters from North Carolina to Maine U.S. Over the years, a number of lessons have been learned about recruiting and supporting industry partners, managing the data, evolving technical specifications, and the challenges associated with analyzing and applying self-reported fisheries data. Here we describe the current state of the program and provide summaries of the Study Fleet program operations and outcomes from 2007-2020, with an eye towards successes, challenges, and applicability of the approach in other regions. We suggest other reference fleet programs, as well as other developing fishery dependent data collections (e.g., electronic monitoring programs), develop detailed roadmaps for each data collection to keep participants engaged as collaborators, target specific fisheries to keep resources from being stretched too thin, and partner with data users early. Additionally, we suggest programs invest in the long-term participation of individual fishermen, carefully weigh the pros and cons of involvement in regulatory reporting, and plan data products and applications well in advance to ensure that the sampling scheme and granularity of the data meet the needs of stock assessment, ecosystem, and oceanographic scientists.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Parasitization of the sugarcane aphid, Melanaphis sacchari, by commercially available aphid parasitoids - Nathan H. Mercer; Ricardo T. Bessin; John J. Obrycki (BioControl, 2021)

Sighting patterns reveal unobserved pupping events to revise reproductive rate estimates for Hawaiian monk seals in the main Hawaiian Islands - Stacie J. Robinson; Albert L. Harting; Tracy Mercer; Thea C. Johanos; Jason D. Baker; Charles L. Littnan (Marine Mammal Science, 2021)
We used sighting reports, including decades of citizen‐reported Hawaiian monk seal ( Neomonachus schauinslandi ) sightings, to describe female breeding biology and reproductive success in the main Hawaiian Islands. We first used this data set to describe the timing of events in the female reproductive cycle. We then conducted an expert review of patterns in sighting histories to detect unobserved pupping events. Finally, we estimated the age‐specific reproductive curve for female monk seals in the main Hawaiian Islands. Charting reproductive cycles showed indications of the robust condition of female monk seals in the main Hawaiian Islands; they nursed pups 12% longer than their counterparts in the Northwestern Hawaiian Islands and regained condition to molt more quickly after weaning a pup. By examining sighting histories, we were able to infer 25 unobserved pupping events that had previously gone uncounted. We accounted for additional uncertainty with a randomization procedure. After accounting for unobserved pupping events, the age‐specific reproductive rate of main Hawaiian Islands monk seals exceeded 0.70 for prime aged females (8–18 years). This is the highest reproductive rate reported for any of the Hawaiian monk seal breeding sites, illustrating the important role of the main Hawaiian Islands population in Hawaiian monk seal recovery.

Scale‐dependent patterns of metacommunity structuring in aquatic organisms across floodplain systems - Fernando M. Lansac‐Tôha; Luis M. Bini; Jani Heino; Bianca R. Meira; Bianca T. Segovia; Carla S. Pavanelli; Claudia C. Bonecker; Claudia P. de Deus; Evanilde Benedito; Geziele M. Alves; Gislaine I. Manetta; Juliana D. Dias; et al. (Journal of Biogeography, 2021)
Aim Evaluating how groups of organisms vary in dispersal capability and how environmental, spatial and temporal signals vary across multiple scales is critical to elucidating metacommunity theory. We examined whether the relative contributions of environmental, spatial and hydrological factors have different effects on organismal groups with different dispersal abilities at three spatial scales, and how this knowledge contributes to our understanding of metacommunity dynamics. Location Four major Brazilian floodplains, with the largest distance among them of 2,300 Km. Taxon 10 aquatic organismal groups, ranging from bacterioplankton to fish. Methods We sampled lakes connected to the main river in the low‐ and high‐water periods of each floodplain between 2011 and 2012. Different biological groups were analysed across three hierarchical spatial scales (fine, intermediate and subcontinental) within and between floodplain systems. We applied a series of partial redundancy analyses to estimate the relative contributions of environmental factors, spatial factors and hydrological period for each biological group. Results At the fine spatial scale, predominantly environmental factors and hydrological period structure metacommunities, although less so for microorganisms than for micro‐invertebrates and macro‐organisms. The relative importance of environmental factors increased at the intermediate spatial scale. At the subcontinental scale, the relative importance of spatial factors increased for all biological groups, but environmental factors remained the primary regulators of microorganisms even at the largest scale. Main conclusions This study design allowed us to make more robust inferences about the mechanisms responsible for regulating community structure of distinct biological groups at different spatial scales. Our results suggest that biological groups displaying distinct body size likely determine the spatial extent at which environmental, spatial and hydrological processes prevail as the primary regulators of community structure. These findings are important in guiding the conservation and management of floodplain biodiversity because these systems are naturally highly heterogeneous in space and time.

Population‐level impacts of natural and anthropogenic causes‐of‐death for Hawaiian monk seals in the main Hawaiian Islands - Albert L. Harting; Michelle M. Barbieri; Jason D. Baker; Tracy A. Mercer; Thea C. Johanos; Stacie J. Robinson; Charles L. Littnan; Katie M. Colegrove; Dave S. Rotstein (Marine Mammal Science, 2021)
Identifying, assessing, and ranking the impact of individual threats is fundamental to the conservation and recovery of rare and endangered species. In this analysis, we quantify not only the frequency of specific causes‐of‐death (CODs) among Main Hawaiian Island (MHI) monk seals, but also assess the impact of individual CODs on the intrinsic growth rate, λ, of the MHI population. We used gross necropsy results, histopathology, and other evidence to assign probabilities of 11 COD types to each mortality and then used Monte Carlo sampling to evaluate the influence of each COD on λ. By right censoring realizations involving specific CODs, we were able to estimate λ (and its associated uncertainty) when CODs were selectively removed from influencing survival. Applying the analysis to all known and inferred deaths believed to have occurred 2004–2019, the CODs with the largest influence on λ were anthropogenic trauma, anthropogenic drowning, and protozoal disease. In aggregate, anthropogenic CODs had a larger effect on the growth rate than either natural or disease CODs. Possible bias associated with differential carcass detection, recovery, and COD classification are discussed.

Land use and land cover control on the spatial variation of dissolved organic matter across 41 lakes in Mississippi, USA - M. S. Sankar; Padmanava Dash; YueHan Lu; Andrew E. Mercer; Gray Turnage; Cory M. Shoemaker; Shuo Chen; Robert J. Moorhead (Hydrobiologia, 2020)

Learning from the history of disaster vulnerability and resilience research and practice for climate change - I. Kelman; J. C. Gaillard; James Lewis; Jessica Mercer (Natural Hazards, 2016)

Measurements of Chlorpyrifos Levels in Forager Bees and Comparison with Levels that Disrupt Honey Bee Odor-Mediated Learning Under Laboratory Conditions - Elodie Urlacher; Coline Monchanin; Coraline Rivière; Freddie-Jeanne Richard; Christie Lombardi; Sue Michelsen-Heath; Kimberly J. Hageman; Alison R. Mercer (Journal of Chemical Ecology, 2016)

The New Zealand experience of varroa invasion highlights research opportunities for Australia - Jay M. Iwasaki; Barbara I. P. Barratt; Janice M. Lord; Alison R. Mercer; Katharine J. M. Dickinson (Ambio, 2015)

Understanding the Chronic Impacts of Oil Refinery Wastewater Requires Consideration of Sediment Contributions to Toxicity - Jennifer R. Loughery; Tim J. Arciszewski; Karen A. Kidd; Angella Mercer; L. Mark Hewitt; Deborah L. MacLatchy; Kelly R. Munkittrick (Archives of Environmental Contamination and Toxicology, 2014)

Public engagement on solar radiation management and why it needs to happen now - Wylie A. Carr; Christopher J. Preston; Laurie Yung; Bronislaw Szerszynski; David W. Keith; Ashley M. Mercer (Climatic Change, 2013)

Parkinson disease loci in the mid-western Amish - M. F. Davis; A. C. Cummings; L. N. D’Aoust; L. Jiang; D. R. Velez Edwards; R. Laux; L. Reinhart-Mercer; D. Fuzzell; W. K. Scott; M. A. Pericak-Vance; S. L. Lee; J. L. Haines (Human Genetics, 2013)

Production and Evaluation of an Antimicrobial Peptide-Containing Wafer Formulation for Topical Application - Noelle H. O’Driscoll; Olga Labovitiadi; T. P. Tim Cushnie; Kerr H. Matthews; Derry K. Mercer; Andrew J. Lamb (Current Microbiology, 2013)

Age- and behaviour-related changes in the expression of biogenic amine receptor genes in the antennae of honey bees (Apis mellifera) - Henry J. McQuillan; Andrew B. Barron; Alison R. Mercer (Journal of Comparative Physiology A, 2012)

Loopholes in the regulation of invasive species: genetic identifications identify mislabeling of prohibited aquarium plants - Ryan A. Thum; Amanda T. Mercer; Dustin J. Wcisel (Biological Invasions, 2012)

Mitochondrial Haplogroup X is associated with successful aging in the Amish - Monique D. Courtenay; John R. Gilbert; Lan Jiang; Anna C. Cummings; Paul J. Gallins; Laura Caywood; Lori Reinhart-Mercer; Denise Fuzzell; Claire Knebusch; Renee Laux; Jacob L. McCauley; Charles E. Jackson; et al. (Human Genetics, 2012)

RNase 1 genes from the family Sciuridae define a novel rodent ribonuclease cluster - Steven J. Siegel; Caroline M. Percopo; Kimberly D. Dyer; Wei Zhao; V. Louise Roth; John M. Mercer; Helene F. Rosenberg (Mammalian Genome, 2009)

Heterozygous tx mice have an increased sensitivity to copper loading: Implications for Wilson’s disease carriers - Daphne M. Y. Cheah; Yolanda J. Deal; Paul F. A. Wright; Nicole E. Buck; Chung Wo Chow; Julian F. B. Mercer; Katrina J. Allen (BioMetals, 2007)

Microglial Activation is Required for Aβ Clearance After Intracranial Injection of Lipopolysaccharide in APP Transgenic Mice - Donna L. Herber; Mary Mercer; Lisa M. Roth; Keisha Symmonds; Jessica Maloney; Nedda Wilson; Melissa J. Freeman; Dave Morgan; Marcia N. Gordon (Journal of Neuroimmune Pharmacology, 2007)

Breeding for success: diversity in action - A. J. Conner; C. F. Mercer (Euphytica, 2007)

Chronological changes in tissue copper, zinc and iron in the toxic milk mouse and effects of copper loading - Katrina J. Allen; Nicole E. Buck; Daphne M. Y. Cheah; Sophie Gazeas; Prithi Bhathal; Julian F. B. Mercer (BioMetals, 2006)

Photoperiod regulates leptin sensitivity in field voles, Microtus agrestis - E. Król; J. S. Duncan; P. Redman; P. J. Morgan; J. G. Mercer; J. R. Speakman (Journal of Comparative Physiology B, 2006)

Mitochondrial DNA variation in the European lobster (Homarus gammarus) throughout the range - A. Triantafyllidis; A. P. Apostolidis; V. Katsares; E. Kelly; J. Mercer; M. Hughes; K. E. Jrstad; A. Tsolou; R. Hynes; C. Triantaphyllidis (Marine Biology, 2005)

A microsatellite map of white clover - B. Barrett; A. Griffiths; M. Schreiber; N. Ellison; C. Mercer; J. Bouton; B. Ong; J. Forster; T. Sawbridge; G. Spangenberg; G. Bryan; D. Woodfield (Theoretical and Applied Genetics, 2004)

A small molecule antagonist of the α v β3 integrin suppresses MDA-MB-435 skeletal metastasis - John F. Harms; Danny R. Welch; Rajeev S. Samant; Lalita A. Shevde; Mary E. Miele; Geetha R. Babu; Steven F. Goldberg; Virginia R. Gilman; Donna M. Sosnowski; Dianalee A. Campo; Carol V. Gay; Lynn R. Budgeon; et al. (Clinical & Experimental Metastasis, 2004)

Construction of a recombinant orf virus that expresses an Echinococcus granulosus vaccine antigen from a novel genomic insertion site - B. J. Marsland; D. J. Tisdall; D. D. Heath; A. A. Mercer (Archives of Virology, 2003)

An historical overview of the Republic of Ireland's lobster (Homarus gammarus Linnaeus) fishery, with reference to European and North American (Homarus americanus Milne Edwards) lobster landings - R. M. Browne; J. P. Mercer; M. J. Duncan (Hydrobiologia, 2001)

Littoral Acari of Marion Island: ecology and extreme wave action - P. J. A. Pugh; R. D. Mercer (Polar Biology, 2001)

Mite and insect zonation on a Marion Island rocky shore: a quantitative approach - R. D. Mercer; S. L. Chown; D. J. Marshall (Polar Biology, 2000)

Lack of an effect of zolmitriptan (Zomig, 311C90) on psychometric task performance: results of a placebo-controlled study in healthy volunteers - A. J. Mercer; R. J. Lamb; P. E. Rolan; M. Gibbens; J. Posner (Psychopharmacology, 1998)

The reactivity of monoclonal antibodies against orf virus with other parapoxviruses and the identification of a 39 kDa immunodominant protein - F. M. T. Housawi; G. M. Roberts; J. A. Gilray; I. Pow; H. W. Reid; P. F. Nettleton; K. J. Sumption; M. H. Hibma; A. A. Mercer (Archives of Virology, 1998)

Orf Virus Encodes a Homolog of the Vaccinia Virus Interferon-Resistance Gene E3L - Colin J. McInnes; Ann R. Wood; Andrew A. Mercer (Virus Genes, 1998)

Thermogenic responses to body cooling during fever induced by Staphylococcus aureus cell walls in rabbits - Ø. Tøien; J. B. Mercer (Journal of Comparative Physiology B, 1998)

Organochlorines in pleuronectidae: Comparison between three tissues of three species inhabiting the Northwest Atlantic - J. Hellou; W.G. Warren; G. Mercer (Archives of Environmental Contamination and Toxicology, 1995)

In vitro recognition of an orf virus early promoter in a vaccinia virus extract - J. C. Vos; A. A. Mercer; S. B. Fleming; A. J. Robinson (Archives of Virology, 1992)

Orf virus and vaccinia virus do not cross-protect sheep - A. J. Robinson; A. A. Mercer (Archives of Virology, 1988)

s 59th annual meeting Potato Association of America - D. E. Hudson; M. D. Volz; B. B. DePhillips; Gene A. Mathia; Frank Haynes; N. A. Wynn; Allen E. Abrahams; Lewis A. Schaper; Paul H. Orr; Earl C. Yaeger; Combs Joseph; Robert L. Mercer; et al. (American Journal of Potato Research, 1975)

The influence of ammonium nitrate on the fine structure of nodules of medicago tribuloides Desr. and trifolium subterraneum L. - P. J. Dart; F. V. Mercer (Archives of Microbiology, 1965)

Fine structure changes in the development of the nodules of Trifolium subterraneum L. and Medicago tribuloides Desr. - P. J. Dart; F. V. Mercer (Archives of Microbiology, 1964)

The legume Rhizosphere - P. J. Dart; F. V. Mercer (Archives of Microbiology, 1964)

Development of the bacteroid in the root nodule of barrel medic (Medicago tribuloides Desr.) and subterraneum clover (Trifolium subterraneum L.) - P. J. Dart; F. V. Mercer (Archives of Microbiology, 1963)

The intracytoplasmic membrane system of the bacteroids of subterraneum clover nodules (Trifolium subterraneum L.) - P. J. Dart; F. V. Mercer (Archives of Microbiology, 1963)